Changing social inequality from first farmers to early states in Southeast Asia - Fochesato, M; Higham, C; Bogaard, A; Castillo, CC (National Academy of Sciences, 2021)
When the first rice farmers expanded into Southeast Asia from the north about 4,000 y ago, they interacted with hunter-gatherer communities with an ancestry in the region of at least 50 millennia. Rigorously dated prehistoric sites in the upper Mun Valley of Northeast Thailand have revealed a 12-phase sequence beginning with the first farmers followed by the adoption of bronze and then iron metallurgy leading on to the rise of early states. On the basis of the burial rituals involving interment with a wide range of mortuary offerings and associated practices, we identify, by computing the values of the Gini coefficient, at least two periods of intensified social inequality. The first occurred during the initial Bronze Age that, we suggest, reflected restricted elite ownership of exotic valuables within an exchange choke point. The second occurred during the later Iron Age when increased aridity stimulated an agricultural revolution that rapidly led to the first state societies in mainland Southeast Asia.